2019
DOI: 10.1093/infdis/jiz465
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Adipose Tissue Is Associated With Alterations in Tryptophan-Kynurenine Metabolism and Markers of Systemic Inflammation in People With Human Immunodeficiency Virus

Abstract: Background While both adipose tissue accumulation and tryptophan metabolism alterations are features of human immunodeficiency virus (HIV) infection, their interplay is unclear. We investigated associations between abdominal adipose tissue, alterations in kynurenine pathway of tryptophan metabolism, and systemic inflammation in people with HIV (PWH). Methods Eight hundred sixty-four PWH and 75 uninfected controls were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Furthermore, in the interaction analysis, we found that dietary tryptophan interacted with abdominal obesity on obesity risk and interacted with sex on T2D risk. Abdominal obesity has been reported to upregulate indoleamine 2, 3‐dioxygenase activity by chronic immune‐mediated inflammation and then decrease tryptophan availability for the synthesis of serotonin and melatonin, which are the key players in the caloric intake regulation (32,36). This provides evidence for our finding that dietary tryptophan decreased obesity risk, especially in those without abdominal obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the interaction analysis, we found that dietary tryptophan interacted with abdominal obesity on obesity risk and interacted with sex on T2D risk. Abdominal obesity has been reported to upregulate indoleamine 2, 3‐dioxygenase activity by chronic immune‐mediated inflammation and then decrease tryptophan availability for the synthesis of serotonin and melatonin, which are the key players in the caloric intake regulation (32,36). This provides evidence for our finding that dietary tryptophan decreased obesity risk, especially in those without abdominal obesity.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether perturbed glutamate homeostasis is also involved in other non-AIDS-associated comorbidities like MetS is still unknown. Abdominal adipose tissue accumulation, a well-known determinant of MetS in PLWH, has been previously suggested to be associated with increase macrophage infiltration and activation [ 20 ]. It may be speculated that alterations in macrophage glutamate metabolism in the abdominal tissue are also involved in MetS in PLWH.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal adipose tissue accumulation, a well-known determinant of MetS in PLWH, has been previously suggested to be associated with increase macrophage infiltration and activation. 26 It may be speculated that alterations in macrophage glutamate metabolism in the abdominal tissue are also involved in MetS in PLWH.…”
Section: Discussionmentioning
confidence: 99%